All-optical nonequilibrium pathway to stabilising magnetic Weyl semimetals in pyrochlore iridates. Issue 1 (December 2018) - Topp, Gabriel; Tancogne-Dejean, Nicolas; Kemper, Alexander; Rubio, Angel; Sentef, Michael
Abstract Nonequilibrium many-body dynamics is becoming a central topic in condensed matter physics. Floquet topological states were suggested to emerge in photodressed bands under periodic laser driving. Here we propose a viable nonequilibrium route without requiring coherent Floquet states to reach the elusive magnetic Weyl semimetallic phase in pyrochlore iridates by ultrafast modification of the effective electron-electron interaction with short laser pulses. Combining ab initio calculations for a time-dependent self-consistent light-reduced HubbardU and nonequilibrium magnetism simulations for quantum quenches, we find dynamically modified magnetic order giving rise to transiently emerging Weyl cones that can be probed by time- and angle-resolved photoemission spectroscopy. Our work offers a unique and realistic pathway for nonequilibrium materials engineering beyond Floquet physics to create and sustain Weyl semimetals. This may lead to ultrafast, tens-of-femtoseconds switching protocols for light-engineered Berry curvature in combination with ultrafast magnetism. Topological states may emerge in nonequilibrium but the mechanisms are much less understood. Here Topp et al. propose a nonequilibrium route to obtain the magnetic Weyl semimetallic phase in pyrochlore iridates by ultrafast modification of the effective electron-electron interactions with short laser pulses.